2007
DOI: 10.1029/2006jb004575
|View full text |Cite
|
Sign up to set email alerts
|

First‐order reversal curve (FORC) diagrams of natural and cultured biogenic magnetic particles

Abstract: [1] First-order reversal curve (FORC) diagrams are rapidly becoming a standard tool for characterizing magnetic particles because they simultaneously incorporate information regarding magnetostatic interaction and domain states. The simplest interpretation of FORC diagrams of single-domain (SD) particles is based on the Neel interpretation of Preisach theory, which predicts that the FORC function is the product of a coercivity and an interaction field distribution. Although the underlying assumptions of this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…The magnetofossil component is correlated to the medium-coercivity component 2 (Table 1) with coercivity values around 40 mT and a small DP (~0.3), similar to the IRM signal of magnetotactic bacteria found in other studies (e.g. Egli, 2004;Chen et al, 2007;Jovane et al, 2012;Roberts et al, 2012 and 52%. The low-coercivity component varies from 5% to 17%.…”
Section: Environmental Magnetismsupporting
confidence: 83%
“…The magnetofossil component is correlated to the medium-coercivity component 2 (Table 1) with coercivity values around 40 mT and a small DP (~0.3), similar to the IRM signal of magnetotactic bacteria found in other studies (e.g. Egli, 2004;Chen et al, 2007;Jovane et al, 2012;Roberts et al, 2012 and 52%. The low-coercivity component varies from 5% to 17%.…”
Section: Environmental Magnetismsupporting
confidence: 83%
“…Such spreading has been documented in FORC diagrams (cf. Figure 4) for samples that contain disrupted magnetosome chains [ Chen et al , 2007; Egli et al , 2010; Kind et al , 2011]. Regardless, these data indicate that the studied ‘PSD’‐like clay‐rich sediments (Figure 3) contain significant concentrations of previously unrecognized magnetite magnetofossils (Figure 12).…”
Section: Searching For Sd Magnetite In Diverse Sedimentary Environmentsmentioning
confidence: 92%
“…The FORC distribution peaks consistently occur at ∼20 mT and are vertically spread, but they also narrow at higher coercivities. This horizontal ‘tear‐drop’ distribution could indicate significant disruption of magnetofossil chains, with a smaller contribution from non‐disrupted chains [ Chen et al , 2007; Egli et al , 2010]. However, it could also result from detrital SD magnetite from extrusive rocks of the McMurdo Volcanic Group [ Verosub et al , 2000].…”
Section: Searching For Sd Magnetite In Diverse Sedimentary Environmentsmentioning
confidence: 99%
“…The FORC diagram is able to reflect the chain-chain interactions, the intrachain interactions (particle-particle interaction within a chain), and cell-cell interactions (7,33). The vertical spread of FORC contours (H b1/2 ϭ 5.3 mT) in the present study is comparable to that of multiple-chain MTB reported previously (H b1/2 ϭ 6.3 mT) (33) but more prominent than that of single-chain AMB-1 (H b1/2 ϭ 2.4 mT) (21).…”
Section: Vol 75 2009 Characterization Of Uncultivated Magnetotacticmentioning
confidence: 99%